A study of some aspects of classification and grouping : a thesis presented in partial fulfilment of the requirements for an M.A. paper - Jenkins, Annette Patricia (Massey University, 1975)
This investigation is concerned with how children group objects and with the underlying rules they may use to categorize experience. The sample consisted of three hundred and twenty children with equal numbers of boys and girls in each group of eighty, five, eight, ten and twelve year olds. Subjects were given two free sorting tasks using attribute blocks and an array of everyday objects. Verbal explanations were recorded. Developmental trends were sought in terms of the numbers of groups formed (discrimination), criteria chosen as the basis for grouping, and the potency of stimulus material as a possible determinant of criteria. The differences in logical sorting, pattern making and figural arrangements were examined and also found to be age rather than sex related. Language responses showed increasing sophistication in criterial choice and in the ability to explain groupings. Highly significant results were obtained showing age related trends for all groups. Younger subjects formed more groups which they were less able to explain than older children. Younger children showed more responses with partial logic and simple pairing of objects, and they also formed groups on the basis of perceptible (colour, shape, size), while older children used more functional criteria (use). Older subjects showed greater stability in logical grouping and formed fewer groups, each with more objects. Attribute blocks evoked more geometric pictorial and pattern making in younger children than did array materials. Significance was not found for any of the independent variables except age. These included sex, age, parental occupation, size of family, position in the family, pre-school and school attendance.
Keywords: Child development; Child psychology